The Integration of One-Stop Integrated Service Policy in the Religious Judicial System in Indonesia - Lahaji Lahaji; Aisma Maulasa (Al-Ulum, 2023)
This study aims to depict the problems faced in the implementation of a one-stop integrated service policy in the religious judicial system. Data were also obtained through direct interviews from a number of informants, mainly the judges of the provincial and district High Religious Courts (Pengadilan Tinggi Agama) and (Pengadilan Agama). This study finds out that competence of judges in religious courts was minimal, and their selection requirements were laxer, as there were no special criteria for studying Islamic sciences. Consequently, judges preferring decisions on material laws over Islamic precepts. Therefore, judges’ decisions in establishing regulations tend to be fixed on material laws, which is evident in cases such as, divorce lawsuits.